An internal-variable rod model for stress-induced phase transitions in a slender SMA layer. I. asymptotic equations and a two-phase solution - Wang, Jiong; Dai, Hui-Hui (Mechanics of Materials, 2012)
In part I of this series of two papers, an internal-variable rod model is proposed to study the stress-induced phase transitions in a slender shape memory alloy (SMA) layer. To study the mechanical responses of SMAs, two independent energy functions are adopted: the Helmholtz free energy and the rate of mechanical dissipation. A phase state variable is introduced to describe the phase transition process. Starting from the 2-D governing system and by using the coupled series-asymptotic expansion method, one single equilibrium equation is derived, which involves the leading order term of the axial strain and the phase state functions. Further by using the phase transition criteria, the evolution laws of the phase state functions corresponding to the outer loop of the stress-strain response are derived. As a result, the governing ODEs for the purely loading and purely unloading processes are obtained, which are called the asymptotic rod equations. The two-phase solution of the asymptotic rod equations in an infinitely long layer is then constructed. An explicit solution for the phase volume fraction of the corresponding inhomogeneous deformation is deduced, which appears to be the first analytical expression for this important quantity in stress-induced phase transitions. The key parameters in terms of original material constants for the phase transitions and deformations are also identified. © 2011 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-TM.aninte